Nanomaterials for structural, functional and biomedical applications : selected, peer reviewed papers from the Russian-German Forum on Nanotechnology May 21-24, 2013, Tomsk, Russia - Khasanov, Oleg (Advanced materials research, 2014)
Collection of selected, peer reviewed papers from the Russian-German Forum on Nanotechnology, May 21-24, 2013, Tomsk, Russia. The 43 papers are grouped as follows: Chapter 1: Advanced Materials: Synthesis, Structure and Application; Chapter 2: Novel Processing for Improving Materials; Chapter 3: Biomedical Aspects of Nanomaterials The forum was held to strengthen the established contacts between Russian and German scientists, to enhance scientific and technical cooperation in fundamental and applied nanotechnology, and to identify topics that might lead to joint research and development cluste.